The Thought and Methodology of Al-Baghawi in Masabih al-Sunnah: Implications for Contemporary Hadith Studies - Fatoni, Ahmad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2025)
This research comprehensively examines the book Masabih al-Sunnah, focusing on its methodology, al-Baghawi's distinctive and controversial terminologies, and and the implications for the study of Contemporary Hadith. The study employs a descriptive-analytical method to outline the book’s fundamental structure and critically elaborate on its content. The approach utilized is a book analysis study (bahth al-kutub), which analyze both the structure and methodology employed by the author. Based on the composition of the book, it can be concluded that, al-Baghawi tends to use the al-jawami' method, which invilve omitting the sanad of the hadiths, except for the names of companions when necessary. In this book, the term al-Sihhah refers to all the hadiths narrated by Bukhari and Muslim in the Sahihayn. While the term al-Hisan refers to the hadiths narrated by Abu Dawud, al-Tirmidhi, and other imam of hadith. Al-Baghawi’s work includes 28 chapters, 277 subchapters, and a total of 4.931 hadiths, of which 2.504 are classified as ṣaḥīḥ and 2.432 as ḥasan.